Does global change increase the risk of maladaptation of Atlantic salmon migration through joint modifications of river temperature and discharge?. Issue 1964 (8th December 2021) - Arevalo, Elorri; Maire, Anthony; Tétard, Stéphane; Prévost, Etienne; Lange, Frédéric; Marchand, Frédéric; Josset, Quentin; Drouineau, Hilaire
Abstract : In freshwater ecosystems, water temperature and discharge are two intrinsically associated triggers of key events in the life cycle of aquatic organisms such as the migration of diadromous fishes. However, global changes have already profoundly altered the thermal and hydrological regimes of rivers, affecting the timing of fish migration as well as the environmental conditions under which it occurs. In this study, we focused on Atlantic salmon ( Salmo salar ), an iconic diadromous species whose individuals migrate between marine nursery areas and continental spawning grounds. An innovative multivariate method was developed to analyse long-term datasets of daily water temperature, discharge and both salmon juvenile downstream and adult upstream migrations in three French rivers (the Bresle, Oir and Nivelle rivers). While all three rivers have gradually warmed over the last 35 years, changes in discharge have been very heterogeneous. Juveniles more frequently used warmer temperatures to migrate. Adults migrating a few weeks before spawning more frequently used warm temperatures associated with high discharges. This has already led to modifications in preferential niches of both life stages and suggests a potential mismatch between these populations' ecological preference and changes in their local environment due to global change.